Prenatal stress changes the glycoprotein GPM6A gene expression and induces epigenetic changes in rat offspring brain - Monteleone, Melisa Carolina (2014)
Prenatal stress (PS) exerts strong impact on fetal brain development and on adult offspring brain functions. Previous work demonstrated that chronic stress alters the mRNA expression of GPM6A, a neuronal glycoprotein involved in filopodium extension. In this work, we analyzed the effect of PS on gpm6a expression and the epigenetic mechanisms involved. Pregnant Wistar rats received restraint stress during the last week of gestation. Male offspring were sacrificed on postnatal days 28 and 60. Hippocampus and prefrontal cortex samples were analyzed for gene expression (qPCR for mRNAs and microRNAs), methylation status (bisulfite conversion) and protein levels. Hippocampal neurons in culture were used to analyze microRNA overexpression effects. Prenatal stress induced changes in gpm6a levels in both tissues and at both ages analyzed, indicating a persistent effect. Two CpG islands in the gpm6a gene were identified. Variations in the methylation pattern at three specific CpGs were found in hippocampus, but not in PFC samples from PS offspring. microRNAs predicted to target gpm6a were identified in silico. qPCR measurements showed that PS modified the expression of several microRNAs in both tissues, being microRNA-133b the most significantly altered. Further studies overexpressing this microRNA in neuronal cultures showed a reduction in gmp6a mRNA and protein level. Moreover filopodium density was also reduced, suggesting that GPM6A function was affected. Gestational stress affected gpm6a gene expression in offspring likely through changes in methylation status and in posttranscriptional regulation by microRNAs. Thus, our findings propose gpm6a as a novel target for epigenetic regulation during prenatal stress.